1960
DOI: 10.2134/agronj1960.00021962005200040009x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Utilization in High and Low Protein Wheat Varieties1

Abstract: Synopsis No differences were found in total nitrogen content of vegetative parts of high and low protein wheat varieties prior to heading. After heading nitrogen increased more rapidly in the heads of high protein varieties. Varietal differences in protein content of the kernels were not decreased by growing plants in solution culture, or by foliar applications of urea or nitrate nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1977
1977
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 1 publication
1
11
1
Order By: Relevance
“…The same authors reported that the major factors responsible for variation in grain protein content are climate, soil fertility and genotype. The benefits of applying nitrogen fertilizer to increase both yield and grain protein levels in wheat have been reported by many research workers (McNeal & Davis, 1954;Finney, Meyer, Smith & Fryer, 1957;Seth, Herbert & Middleton, 1960;Alkier, Raczs & Soper, 1972;Strong, 1982;Randall, Freney, Smith, Moss, Wrigley & Gallaby, 1990). Inverse relationships between protein content of wheat grains and yield level have also been reported (Malloch & Newton, 193.4;Terman, Ramig, Dreier &.…”
Section: Grain Protein Content Per Earmentioning
confidence: 90%
“…The same authors reported that the major factors responsible for variation in grain protein content are climate, soil fertility and genotype. The benefits of applying nitrogen fertilizer to increase both yield and grain protein levels in wheat have been reported by many research workers (McNeal & Davis, 1954;Finney, Meyer, Smith & Fryer, 1957;Seth, Herbert & Middleton, 1960;Alkier, Raczs & Soper, 1972;Strong, 1982;Randall, Freney, Smith, Moss, Wrigley & Gallaby, 1990). Inverse relationships between protein content of wheat grains and yield level have also been reported (Malloch & Newton, 193.4;Terman, Ramig, Dreier &.…”
Section: Grain Protein Content Per Earmentioning
confidence: 90%
“…at maturity was due to differential niffogen Seth et al (1960) and Johnson et al uptake. (1967Johnson et al uptake.…”
mentioning
confidence: 99%
“…Only Oroua, V763-17, and V763-252 appeared to respond to higher rates of applied nitrogen. The late application of urea probably prevented a consistent response (Seth et al 1960). The highest plant dry weights were recorded from BTL, V763-252, and V763-2332.…”
Section: Resultsmentioning
confidence: 99%
“…Differences between "high protein" and "low protein" cultivars have been related to the efficiency of nitrogen translocation from the various organs to the developing seed (Seth et al 1960;Johnson et al 1969). Kushnir & Halloran (1984) showed differences in efficiency of translocation of metabolised nitrogen from the plant into the grain in tetraploid and hexaploid wheats.…”
Section: Introdljctionmentioning
confidence: 99%